RC Infilling of Existing RC Structures for Seismic Retrofitting - Chrysostomou, Christis; Kyriakides, Nicholas; Poljanšek, Martin; Taucer, Fabio; Molina, Francisco Javier (My University, 2013)
The effectiveness of seismic retrofitting of multi-storey multi-bay RC-frame buildings by converting selected bays into new walls through infilling with reinforced concrete (RC) was studied experimentally at the ELSA facility of the Joint Research Centre in Ispra (Italy). A full-scale structure was tested with the pseudo-dynamic method. It consisted of 2 four-storey (12 m tall) three-bay (8.5 m long) parallel frames linked through 0.15 m slabs. The central bay (2.5 m) of each frame is infilled with a RC wall. The frames were designed and detailed for gravity loads only and are typical of similar frames built in Cyprus in the 1970s. Different connection details and reinforcement percentages for the two infilled frames were used in order to study their effects in determining structural response. The results of the pseudo-dynamic and cyclic tests performed on the specimen are presented, and conclusions are drawn.
Keywords: Geotechnical Engineering & Applied Earth Sciences; Structural Mechanics; Civil Engineering; Vibration, Dynamical Systems, Control Natural Hazards